Can common risk factors explain infrastructure equity returns? Evidence from European capital markets. Issue 2 (2nd April 2016) - Wurstbauer, Daniel; Lang, Stephan; Rothballer, Christoph; Schaefers, Wolfgang
Abstract: This is the first paper to test the ability of conventional asset pricing models to explain the excess returns of European infrastructure stocks. Specifically, we firstly run the well-known Fama and French three-factor model, including three common stock market factors (market risk, size risk and value risk), and subsequently augment the model with two common bond risk factors (term and default risk), as infrastructure firms should be closely related to bond markets. The times-series regressions span the period from July 1992 to June 2014 and are conducted using an individually created infrastructure equity data-set. With the help of an intensive screening process, we only include those infrastructure stocks that in fact own and/or operate physical infrastructure. The results reveal that the three-factor model is unable to capture most of the variation in infrastructure returns. Therefore, bond risk factors should be included in asset pricing models in order increase the goodness of fit, as infrastructure stocks prove to be sensitive to interest rate changes. Nevertheless, even the augmented asset pricing model leaves a substantial part of the variance unexplained, thus indicating that infrastructure firms exhibit a high level of idiosyncratic risk. In addition, the results suggest that there may be further risk factors which should be investigated in future studies.